The sedimentology of the diamondiferous Koeskop Palaeochannel of the Lower Orange River, South Africa - Mouton, Eric Louis (Stellenbosch : Stellenbosch University, 2012)
Dissertation (M.Sc) -- University of Stellenbosch, 1999.